THE READINESS OF HUMAN RESOURCES IN THE IMPLEMENTATION OF THE MERAH PUTIH VILLAGE COOPERATIVE - Ferdian Franata; Udin Saripudin; Iwan Permana (El-Ecosy : Jurnal Ekonomi dan Keuangan Islam, 2026)
This study aims to analyze the readiness of Islamic human resources in the implementation of the Village/Urban Village Red and White Cooperative as an agenda for strengthening village economic institutions in Indonesia. This research applies a qualitative approach through literature review and document analysis of regulations, government publications, open-access scientific articles, and Islamic human resource management references. The findings show that the success of the Red and White Village Cooperative is not only determined by legal establishment and business facilities, but also by the readiness of the human resources who manage the cooperative. Such readiness includes technical competence, managerial capability, digital literacy, integrity, understanding of cooperative principles, and internalization of Islamic values such as trustworthiness, justice, competence, excellence, and public benefit. This article proposes a conceptual model for strengthening Islamic human resource management in the Red and White Village Cooperative, consisting of human resource planning, merit-based recruitment and selection, continuous training and mentoring, fair performance and compensation management, and digital participatory governance. The study recommends that the implementation of the Red and White Village Cooperative should not merely pursue quantitative targets, but also strengthen the quality of managers, supervision mechanisms, and member participation